Endocrine Function of Ovarian Tissue Grafts After Normo- and Hypothermic Storage - Kiroshka , Viktoria; Bozhkova , Yulia; Gavas , Ahmed; Rula , Iryna; Bondarenko , Tetyana; Semko , Galyna; Pyatikop, Volodymyr (Problems of Cryobiology and Cryomedicine, 2021)
Morphological characteristics and function of ovarian tissue after 2–120 hrs of storage at 4 and 37°C in incubation media with different composition (mannitol-containing solution (MСS) and phosphate buffered saline (PBS)) were investigated. The function of ovarian tissue after normo- and hypothermic storage was studied by heterotopic transplantation to recipient animals simultaneously with bilateral ovariectomy. After 2-hour storage at 37ºC and 24-hour one at 4ºC in all the studied media, the estradiol and progesterone levels in plasma of recipient animals were experimentally proved to be 18.2–27.5 and 13.5–18.5 ng/ml, respectively, (after fresh tissue transplantation these values for estradiol and progesterone made (28.1 ± 3.6) pg/ml and (19.1 ± 2.8) ng/ml, respectively). Prolongation of tissue storage time at 37ºC increased the number of degenerative follicles, augmented TBARS concentration and reduced sex hormone levels after transplantation using both MCS and PBS. A protective effect of MCS only, manifested in endocrine function restoration in recipient animals after transplantation ((13.5 ± 2.5) pg/ml of estradiol) was found after 48 hrs of ovarian tissue hypothermic storage. If PBS was used, the estradiol level was within the indices for ovariectomized animals ((7.1 ± 1.5 (pg/ml)). Probl Cryobiol Cryomed 2021; 31(4): 326–342